Historien om en kanal: Klimaforandringer og vandpolitik i det peruanske højland - Rasmussen, Mattias Borg (Tidsskriftet Antropologi, 2011)
Klimaforandringerne øger presset på vandressourcerne i det peruanske Andes. Artiklens forfatter følger i tid og rum en vandingskanal i provinsen Recuay i Perus højland. Historisk følges kanalen før, under og efter jordbrugsreformerne. Med inspiration fra Norman Longs Encounters at the Interface (2002) er det muligt at lokalisere et antal interfaces langs kanalen. Gennem en analyse af interfaces og kanalens forløb bliver det muligt at konkludere, at vandmanglen er et resultat af et samspil mellem økologiske og sociale relationer. Til slut fremføres det, at samtidig med at klimaforandringerne øger presset på vandressourcerne, skabes der også nye muligheder for dialog mellem den lokale befolkning og eksperterne. Søgeord: klimaforandring, vand, lokalpolitik, Andes, Peru English: The Story of a Canal. Climate Change and the Politics of Water in the Peruvian Highland Climate change increases pressure upon water resources in the Peruvian Andes, and the issue of water scarcity may become even more pertinent. The exploration of the problematic of water is about the relationship between water and social organization, and the impact of climate change upon that relationship. “The story of a canal” traces the course of an irrigation canal in the Peruvian highland province of Recuay in time and space. The history of the canal is followed through different phases of before, under and after the agrarian reform up until the establishment of the present day peasant communities, thus inserting the course of the canal into historical land tenure dynamics. Following the analytical framework set up by Norman Long in Encounters at the Interface (2001), a number of interfaces of interaction is located along the course. Through an analysis of the interfaces and the course of the canal it is argued that water scarcity is the result of a complex interplay between ecological and social relations. Finally it is argued, that while climate change increases pressure upon water resources, it also can produce new openings through renewed dialogue between the local population and experts. Keywords: Climate change, water, local politics, Andes, Peru